Assessing the impact of fossil fuel subsidies and environmental tax on renewable energy consumption of OECD countries: A panel quantile approach - Priyanshu Chavda; Dhyani Mehta (Next Energy)
In global efforts to achieve net-zero targets, energy consumption from renewable sources is crucial. With this, the gradual elimination of fossil fuel subsidies as an influencing factor for enhancing renewable energy consumption has received less academic interest. Thus, this study aims to investigate the impact of fossil fuel subsidies and environmental taxes on renewable energy consumption in Organization for Economic Cooperation and Development (OECD) countries. The impact was assessed using a panel quantile model, which analysed the annual time series data from 2015 to 2023 of OECD countries. The novelty of this study lies in its use of IMF’s fossil fuel subsidies data, which includes implicit subsidies and accounts for negative externalities, while employing a panel quantile model to capture distributional effects. The coefficient of fossil fuel subsidies is negative and significant, supporting the argument that large fossil fuel subsidies impede the transition to renewables. The positive and significant coefficient for environmental taxes shows that environmental taxation is an important fiscal tool to disincentivize harmful consumption by correcting negative externalities and fostering the adoption of renewable energy. Furthermore, the positive and significant coefficient of Gross Domestic Product (GDP) indicates that higher GDP promotes adoption of renewable energy, thereby supporting the conservative hypothesis. The results show that the effects of subsidies and taxes are heterogeneous, with stronger impacts in countries with a high renewable energy share. These results highlight the importance of gradually removing fossil fuel subsidies and strengthening environmental taxation to accelerate the transition towards green energy. The study offers valuable insights for policymakers seeking to strike a balance economic growth and environmental sustainability.